Hemangiopericitoma de órbita - Zanasi Junior, Sidney (2012)
Hemangiopericytomas are rare tumors arising from the proliferation of pericytes. They may be found in the lungs, bones, skull, deep soft tissue or limbs. The tumor has an unpredictable prognosis and when it affects the orbital region, may have an aggressive behavior, with high incidence of recurrence. We report a case of orbital hemangiopericytoma and highlight clinical, surgical, and histopathological features of these tumors. Orbital hemangiopericytomas usually are solid, slow-growing tumors. They should be considered in the differential diagnosis of well-defined orbital masses along with epidermoid cysts, schwannomas, neurofibromas, fibrous histiocytomas, lipomas, and vascular malformations. The diagnosis is confirmed by anatomopathologic examination and sometimes complemented by immunohistochemistry. Complete excision of the tumor with wide margins is usually curative; however, radiotherapy and chemotherapy may be required for recurrent lesions.